An increased CD25-positive intestinal regulatory T lymphocyte population is dependent upon Cox-2 activity in the Apcmin/+ model. (24th October 2017) - Faluyi, O O; Fitch, P; Howie, S E M
Summary: Only mismatch repair (MMR)-deficient colorectal cancer (CRC) appears to respond well to programmed death (PD)-1 inhibition at the present time. Emerging evidence suggests a role for micro-environmental factors such as CD25 + cells modulating response to PD-1 inhibition. In the Apc Min/+ model of familial adenomatous polyposis (MMR-proficient CRC), increased Cyclooxygenase-2 (Cox-2) expression by cells which include alternatively activated mononuclear phagocytes promotes intestinal tumorigenesis by mechanisms which may include immune suppression. To gain insight into this, we compared regulatory T cell (Treg ) populations between Apc Min/+ and wild-type mice prior to and after the phase of increased intestinal Cox-2 -dependent prostaglandin E2 (PGE2 ) production. There was no difference in systemic Treg function or numbers between Apc Min/+ and wild-type mice. However, increased numbers of small intestinal CD25 + Tregs were observed with increased Cox-2 activity in the absence of any difference in the expression of Tgf-β or Tslp between Apc Min/+ and wild-type mice. Cox-2 inhibitor therapy (Celecoxib) reversed the increase in Apc Min/+ intestinal CD25 + Treg numbers, without decreasing numbers of CD25 + systemic Tregs . Forkhead box protein 3 (FoxP3 + ) and Cox-2 + cells were co-localized to the interstitium of adenomas of Apc min/+ mice. These results suggest selective dependence of an 'activated Treg ' phenotype on paracrine Cox-2 activity in Apc Min/+ small intestine. For therapeutic potential, further studies are required to evaluate the relevance of these findings to human cancer as well as the functional significance of CD25 + intestinal Tregs in cancer. Graphical Abstract: